Neoliberal Transformation of Higher Education: Implications for Quality, Diversity and Intellectual Development - Alhaija, Younis Fareed Abu (An Overview of Literature, Language and Education Research Vol. 2, 2024)
The term neoliberalism symbolizes absolute capitalist policies that call for allowing market freedom to the maximum extent possible, and for reducing the public sector to a minimum. Neoliberalism is an ideological idea based on economic freedom, represented by fully supporting capitalism while limiting state interference with it on the one hand and working to increase the role of the private sector in economic activities as much as possible on the other. On the other hand, higher education institutions play important roles in consolidating the values of society, spreading knowledge and its gains, and activating community participation. Neoliberalism calls for the removal of state and society authority from educational institutions, as a matter of democratization of education and individual freedom. This article aims to examine the impact of neoliberalism on higher education, and the changes that have taken place in universities and colleges. The research method is theoretical and qualitative, and illustrates the progressive impact of neoliberal higher education ideas on higher education institutions and its spread, in order to serve the interests of economic and technological competition and market demands. Despite the increase in the number of institutions of higher education and the multiplicity of private colleges, which enable studies for a growing number of students, there are negative aspects to the approach of higher education; Changes in the cultural and administrative structure and orientation of academic institutions. This liberal trend directly affects the quality of education in addition to the commodification of education. The contributions of the private sector have multiplied in order to produce a professionally trained workforce, capable of integrating into the market and managing business and commerce - at the expense of the humanities, social sciences, arts and critical thinking. Moreover, there is a marked deterioration in the quality of education and its products in terms of academic efficiency and scientific research. The goal of education focuses on creating graduates without scientific or intellectual training, and on social interests. Henceforth, it can be concluded that the effects of neoliberalism were reflected in the relationship between higher education institutions and state politics. Neoliberal policies directly affected the quality of education, in addition to the commodification of education through the proliferation of private higher education institutions for filling the requirements of the market, rather than moral, ethical or liberal aspects. As a result, the quality of education declined, whether in terms of educational outcomes or in terms of academic competence and scientific research.